Worldmaking: Psychology and the Ideology of Creativity - Hanchett Hanson, Michael. author. aut Link
XVIII, 266 p.
Keywords: Michael Hanchett Hanson weaves together the history of the development of the psychological concepts of creativity with social constructivist views of power dynamics and pragmatic insights. He provides an engaging, thought-provoking analysis to interest anyone involved with creativity, from psychologists and educators to artists and philosophers.